How do immune cells shape type 1 diabetes? Insights from Mendelian randomization - Yu, Yunfeng; Yang, Xinyu; Deng, Juan; Wu, Jingyi; Bai, Siyang; Yu, Rong (Frontiers in Endocrinology, 2024)
ObjectiveThe role of immune cells in type 1 diabetes (T1D) is unclear. The aim of this study was to assess the causal effect of different immune cells on T1D using Mendelian randomization (MR).MethodsA dataset of immune cell phenotypes (numbered from GCST0001391 to GCST0002121) was obtained from the European Bioinformatics Institute, while a T1D dataset (numbered finngen_R10_T1D) was obtained from FinnGen. Single nucleotide polymorphisms meeting the conditions were screened stepwise according to the assumptions of association, independence, and exclusivity. Inverse variance weighted was used as the main method for the MR analysis. MR-Egger was used to assess the horizontal pleiotropy of the results. Cochran’s Q and the leave-one-out method were respectively used for the heterogeneity analysis and the sensitivity analysis of the results.ResultsMR analysis showed that effector memory (EM) double-negative (DN) (CD4−CD8−) %T cells [odds ratio (OR) = 1.157, 95% confidence interval (95% CI) = 1.016–1.318, p = 0.028, false discovery rate (FDR) = 0.899], EM CD8br %T cells (OR = 1.049, 95% CI = 1.003–1.098, p = 0.037, FDR = 0.902), CD28 on CD28+CD45RA+CD8br (OR = 1.334, 95% CI = 1.132–1.571, p = 0.001, FDR = 0.044), IgD+CD38dim %lymphocytes (OR = 1.045, 95% CI = 1.002–1.089, p = 0.039, FDR = 0.902), CD80 on monocytes (OR = 1.084, 95% CI = 1.013–1.161, p = 0.020, FDR = 0.834), SSC-A on plasmacytoid dendritic cells (pDCs) (OR = 1.174, 95% CI = 1.004–1.372, p = 0.044, FDR = 0.902), and FSC-A on pDCs (OR = 1.182, 95% CI = 1.011–1.382, p = 0.036, FDR = 0.902) were associated with an increased genetic susceptibility to T1D. Cochran’s Q showed that there was heterogeneity for CD28 on the CD28+CD45RA+CD8br results (p = 0.043), whereas there was no heterogeneity for the other results (p ≥ 0.05). The sensitivity analysis showed that the MR analysis results were robust.ConclusionThe MR analysis demonstrated that seven immune cell phenotypes were associated with an increased genetic susceptibility to T1D. These findings provide a new direction for the pathogenesis of and the drug development for T1D.